The π–π stacking-guided supramolecular self-assembly of nanomedicine for effective delivery of antineoplastic therapies. (9th November 2018) - Yang, Dongjuan; Gao, Shan; Fang, Yan; Lin, Xiaojie; Jin, Xuechao; Wang, Xiyan; Ke, Liyuan; Shi, Kai
In traditional nano drug-delivery systems, the complex chemical bonds between drug and carrier often complicate the preparation process and are less prone to rupture upon entry into the target, which is detrimental to the timely release of the drug. The π–π stacking provides us with a promising alternative as it is a weak interaction between the aromatic rings. Since most antitumor drugs are hydrophobic molecules with complex aromatic π–π-conjugated structures, the construction of self-assembly based on π–π stacking between drugs and carriers has the advantage of improving the stability and drug loading capacity as well as the improvement of hydrophilicity and biosafety. This article introduces the recent advances in π–π stacking-guided nano self-assembly for antineoplastic delivery.